Use of plant growth regulators to increase fruit set of apple orchards covered with anti-hail nets in southern Brazil - Hawerroth F.J. (2020)
© 2020 International Society for Horticultural Science. All rights reserved.The use of anti-hail net has been the main strategy used to minimize the damages caused by hail precipitation in apple orchards in southern Brazil. The light restriction due to the use of anti-hail nets, when combined with climatic conditions of high rainfall and cloudiness, can intensify the vegetative development in the flowering phase, having a significant effect on the reduction of effective fructification. In this sense, the use of plant growth regulators with possible benefits on apple fructification is necessary to improve the yield of orchards covered with anti-hail net. The objective of this work was to evaluate the use of prohexadione calcium (PCa), single and in combination with thidiazuron (TDZ) and aminoethoxyvinylglycine (AVG) on apple fructification parameters under anti-hail nets. The trials were carried out in commercial apple orchards of ‘Galaxy’ and ‘Suprema’s Fuji’ located in Vacaria, RS, Brazil, both covered with black anti-hail net. In the first experiment prohexadione calcium applications were tested in concentrations ranging from 82.5 to 165 g ha-1, in two applications from the beginning of growing. In the second experiment the TDZ were evaluated, single and in combination with PCa and AVG, in one or two applications (pink cluster and petal fall stages) on fructification parameters of ‘Galaxy’ apples. In both trials, the evaluations of fruit set, number of floral clusters with fruit, number of fruits per floral cluster, number of fruits plant-1 were done. The use of prohexadione calcium in two applications (shoots smaller than 5 cm and 21 days after first application) at 82.5 g ha-1 (in each application) is effective to increase fructification of apples trees covered with anti-hail nets in southern Brazilian conditions. The application of thidiazuron at 20 mg L-1 and prohexadione calcium at 110 mg L-1 in the pink cluster stage, and the sequential application of thidiazuron at 20 mg L-1 and aminoethoxyvinylglycine at 60 mg L-1 on petal fall stage, increases ‘Gala’s fructification, with more balanced fruiting distribution into the canopy.